Didactic Opportunities for the Application of Steam Technologies in Primary Education (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article examines the didactic possibilities of STEAM technologies in primary school classes. It analyzes the works of researchers in the field of STEAM technologies. The role of the teacher in applying STEAM technologies in the educational process is highlighted, some examples of developing intrinsic motivation among primary school students are provided, and methods of integrating mathematics with other sciences are demonstrated. Factors enhancing the intrinsic motivation of younger students are also listed.